Caractérisation Socio-Économique des Systèmes de Culture à Base d’igname dans Trois Zones Agro-Écologiques pour une Gestion Durable des Terres au Bénin - Adifon, F. S.; Yabi, I.; Balogoun, I.; Dossou, J.; Saïdou, A. (European Scientific Journal, ESJ, 2019)
In Benin, yam is an important food crop. Nowadays, intensification of this food crop face several constraints as lack of virgin land and fertile soil. The present study aims to characterize yam cropping systems in the centre, north-eastern and north-western of Benin that deal with deforestation and the soil degradation due to extensive yam production. Socio-economic characteristics of the yam producers, and the types of cropping system were assessed from 351 yam producers (114 in the centre, 121 in the North-East and 116 in the North-West) using an open end questionnaire. The respondents were identified with the assistance of the local extension service. The results show that the areas allocated to yam production are 1.20 ± 0.08 ha, 0.91 ± 0.06 ha and 0.80 ± 0.05 ha per producer in the Centre, North-East and North West respectively. Extensive yam production and slash-and-burn clearing generally remain the common practice for yam production in the Centre with high pressure on the lowland areas (76.9% of the respondent). In the NorthEast these cropping systems are less practiced in favor of crop rotation (76.9% of those surveyed). The average yam yields were 9.90 ± 0.25 T ha -1 in the Centre, 9.74 ± 0.36 T ha -1 in the North-East, and 9.64 ± 0.30 T ha -1 in the North-West. The analysis of variance showed non-significant difference (p> 0.05) in yam yields regarding the socio-cultural groups. Rational mineral and organic manure supply, cattle parking system in field and crop rotation with leguminous crops were explored for intensive yam production strategy which will contribute to reduce pressure on natural resources and soil fertility maintenance in the study area. Au Bénin, l’igname représente une culture vivrière de première importance. De nos jours cette spéculation est confrontée au problème de disponibilité de terres vierges pour une intensification de la production.La présente étude a pour but de caractériser les systèmes de production à base d’igname au Bénin. Une collecte de données à l’aide d’un questionnaire administré à 351 producteurs dont 114 au Centre, 121 au Nord-Est et 116 au Nord-Ouest du Bénin a été menée. Ils ont été identifiés selon un échantillonnage aléatoire simple. Les résultats ont montré que les superficies allouées à la culture de l’igname sont de 1,20±0,08 ha par producteur au Centre, 0,91±0,06 ha au Nord-Est et 0,80±0,05 ha au Nord-Ouest. La production extensive d’igname reste une pratique courante dans le Centre avec une pression sur les bas-fonds (47, 1 %). Dans le Nord-Est ces pratiques sont moins observées au profit du système de rotation culturale avec l’igname en tête (76,9% des personnes enquêtées). Les rendements moyens en tubercules sont de 9,90±0,251 T ha -1 dans le Centre, 9,74 ±0,363 T ha -1 dans le Nord-Est et de 9,64±0,302 T ha -1 au Nord-Ouest. L’analyse de la variance a montré une différence non significative (p > 0,05) des rendements d’igname selon les groupes socio-culturels. L’apport raisonné de fumure minérale et organique, les parcages des bovins et l’utilisation des légumineuses comme précédent culture à l’igname ont été mentionnés comme des perspectives pour attenuer la pression des producteurs sur les ressources naturelles et le maintien du niveau de fertilité des sols.